Adaptive current harmonics suppression strategy for grid-tie inverters. (September 2022) - Pan, Zhifeng; Wang, Xiaohong; Guan, Quanxue; Chen, Yangquan; Tian, Lianfang
Abstract: Since the observed angle of a phase-locked loop (PLL) is relatively accurate even under distorted grid conditions, the mathematical model of the voltage errors caused by the switching modulation and the dead-time effect are derived as a function of the grid voltage angle in this paper. Based on the model analysis, an adaptive compensation algorithm is proposed to suppress the grid-side current harmonics in three-phase converters. The proposed algorithm fits the unmeasurable voltage errors by a truncated Fourier series expansion, and then takes it as an equivalent disturbance in the current control loop to achieve harmonic compensation. By the feed-forward compensation, the design and tuning of the controller parameters are simplified and separated from the dynamic performance. In addition, the controller can adapt to the grid frequency variation by updating the grid voltage angle with the PLL block. To reduce the computational burden, a simplified version of the proposed method is also presented. Simulation and experiment results show that the proposed methods can suppress the current harmonics and achieve better performance in terms of total harmonic distortion, strong robustness and insensitivity to the grid frequency variations, compared with the traditional PI control or repetitive control strategy. Graphical abstract: Highlights: A PI controller is designed to ensure satisfactory dynamic performance. An adaptive method is employed to compensate the voltage errors caused by the switching modulation and the deadtime effect so as to suppress the grid current harmonics. A simplified adaptive strategy is also presented to reduce the computational burden and the complexity to half of the original method. The adaptive algorithm is less model-dependent and built based on the grid voltage angle with a PLL to achieve frequency adaption.